STRATEGI DALAM PEMBERDAYAAN PELAKU USAHA KECIL DAN MENENGAH DI KABUPATEN LUWU UTARA - Ina, Ina; Razak, Andi Rosdianti; Khaerah, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this study was to determine the government's strategy in empowering small and medium enterprises in North Luwu Regency. The method used in this study is qualitative with a descriptive approach. The results of the research show that in the process of empowering SMEs with indicators of goals, environment, direction, action and learning as well as supporting and inhibiting factors, the government in Luwu Uara Regency has attempted to empower SMEs in North Luwu . With the aim of improving people's welfare as well as being the driving force of the national economy. Through internal and external environmental factors, namely cooperation and support between the government and business actors, the DP2KUKM government then provides direction, namely by conducting outreach among fellow policy implementing actors and between community policy implementers supported by financial institutions